The Influence of Attachment Styles and Personality Organization on Emotional Functioning After Childhood Trauma - Fuchshuber, Jürgen; Hiebler-Ragger, Michaela; Kresse, Adelheid; Kapfhammer, Hans-Peter; Unterrainer, Human Friedrich (Frontiers in Psychiatry, 2019)
Background: Current literature suggests a tenuous link between childhood trauma, personality organization, adult attachment and emotional functioning in various psychiatric disorders. However, empirical research focusing on the interaction of these concepts is sparse. Therefore, this study intends to investigate the influence of personality organization and attachment dimensions on the relationship between childhood maltreatment and emotional functioning in adult life. In order to assess emotional functioning, we adopted the Affective Neuroscience model of primary emotions, comprising SEEKING, FEAR, ANGER, SADNESS, CARE and PLAY. In addition, the possibly mediational role of primitive defense mechanisms in the relationship between childhood trauma and adult attachment was investigated. Methods: The total sample consisted of 616 non-clinical adults (Age: M = 30; SD = 9.53; 61,9% female). Path analysis was applied in order to investigate interactions between childhood trauma, personality organization, adult attachment and primary emotion dispositions. Results: The findings suggest that childhood trauma significantly predicted deficits in personality organization and insecure attachment (all p < 0.001). Furthermore, a reduced level of personality organization was significantly associated with increased ANGER (p < 0.001), while adult attachment substantially predicted primary emotion dispositions in general. Moreover, Tthe results indicate significant mediational effects of personality organization and attachment dimensions on the relationship between childhood trauma and primary emotions (p < 0.01). The final model was able to explain 48% of the variance in SADNESS, 38% in PLAY, 35% in FEAR, 28% in CARE, 14% in ANGER and 13% in SEEKING. Furthermore, primitive defense partially mediated the relationship between childhood trauma and adult attachment. Discussion: The findings contribute to the understanding of the relationship between childhood maltreatment and impaired emotional functioning in adult life. Furthermore, the importance of personality organization and attachment dimensions for emotion regulation is underlined. Consequently, the treatment of patients with childhood trauma should focus on facilitating the development of more secure attachment patterns and increased personality functioning in order to improve overall emotional functioning. In that regard, overcoming primitive defense strategies might be a promising strategy in influencing insecure attachment patterns.